2017
DOI: 10.18203/2349-3291.ijcp20172690
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin and folate status in malnourished children

Abstract: Background: Vitamin B12 and folate are essential micronutrients which are critical especially during infancy and early childhood as these are periods of rapid growth, development, and increased demand. Malnutrition further increases the risk of these micronutrient deficiency due to poor socioeconomic status, inadequate intake and poor absorption. Aim of present work was to study the cobalamin and folate status in malnourished children.Methods: A hospital based observational study on 80 children suffering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 3 publications
4
19
0
Order By: Relevance
“…2 Lower prevalence in this study could be because the study group was not SAM. A study done by Goyal S et al (2017) in Udaipur in 80 SAM children showed vitamin B12 deficiency in 37.5 % and insufficiency in 11.25 % children with overall prevalence of low vitamin B12 levels of 48.75% similar to our study. 3 The mean vitamin B12 level in the above study was 353.65 ± 330.76 pg/ml which is much lower than that in our study.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2 Lower prevalence in this study could be because the study group was not SAM. A study done by Goyal S et al (2017) in Udaipur in 80 SAM children showed vitamin B12 deficiency in 37.5 % and insufficiency in 11.25 % children with overall prevalence of low vitamin B12 levels of 48.75% similar to our study. 3 The mean vitamin B12 level in the above study was 353.65 ± 330.76 pg/ml which is much lower than that in our study.…”
Section: Resultssupporting
confidence: 89%
“…which may further lead to deterioration of nutritional status of the children because of decreased food intake. [3][4][5] In first two years of life, brain growth and myelination is very rapid and Vitamin B12 deficiency results in restricted myelination, resulting in various neurological and intellectual problems in children including development delay.…”
mentioning
confidence: 99%
“…Over the last few years, the number of cases of vitamin B12 deficiency are increasing as compared to folic acid deficiency. 13 In a study by Chhabra A et al, they concluded that nutritional megaloblastic anaemia occurs commonly in malnourished children; the commonest age is 3-18 months. 15 These children were exclusively breast fed by mothers who have had poor cobalamine levels and undernourished.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1and 2). 13 Folic acid deficiency is seen in 3(3.8%) children (Table 3). Mean Vitamin B12 and folate levels being 384.61 and 8.95 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation